Design of Web Virtual Reality for Job Interview Preparation Simulation - Anggoro, Pius Dian Widi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 11 No 3 (2020): Vol. 11, No. 03 December 2020DO - 10.24843/LKJITI.2020.v11.i03.p02, 2020)
The implementation of Virtual Reality (VR) in education is a breakthrough in using technology to support the teaching-learning system. This study will provide more knowledge about the use of VR in English classes. Students can practice answering interview questions in their own place, as often as they need. Students also can practice answering interview questions. This research is use VR technology in a web platform for job interview simulation cases. In the early stages, the evaluation to review the use of VR technology that running on low-specification smartphones (Low-Cost Device), which require a lower internet connection. The WebVR and React 360 libraries were used to develop the virtual environments and JavaScript for the language. The Web Speech API was used to convert the test into conversations by taking questions from the web service on the Moodle learning platform that was connected to PostgreSQL. The first test methods were the web application performance, then followed by Alpha Testing, a validation test by media and material experts. Than it continued in Beta Testing where a product test by 15 English class students participants. The data collection technique used a questionnaire that has to be answered by the participants. The validity and reliability tests were carried out for product usage test. The results obtained from the assessment of media experts and participant provide an assessment score of 83.10 from the experts and 77.58 from the users. The average score obtained is 80.34 which is included in the feasible category. Therefore, this learning media is ready to be used to support learning in English class.